2.3=(t-1.8)/2

Simple and best practice solution for 2.3=(t-1.8)/2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.3=(t-1.8)/2 equation:



2.3=(t-1.8)/2
We move all terms to the left:
2.3-((t-1.8)/2)=0
We multiply all the terms by the denominator
-((t-1.8)+(2.3)*2)=0
We calculate terms in parentheses: -((t-1.8)+(2.3)*2), so:
(t-1.8)+(2.3)*2
We add all the numbers together, and all the variables
(t-1.8)+4.6
We get rid of parentheses
t-1.8+4.6
We add all the numbers together, and all the variables
t+2.8
Back to the equation:
-(t+2.8)
We get rid of parentheses
-t-2.8=0
We add all the numbers together, and all the variables
-1t-2.8=0
We move all terms containing t to the left, all other terms to the right
-t=2.8
t=2.8/-1
t=-2+0.8/1

See similar equations:

| -6(n-6)=12 | | x/5+x/8=13/14 | | 4(2x+9)=-40+44 | | 3n+1=-6-4n | | 5x–45=–10 | | -4(v-75)=-48 | | 2(t−5)=48 | | 6x+3=5x–20 | | 40=5(d-72) | | X+6÷3=2x÷4 | | -36=-6(f-78) | | 9(m−3)+3m=7m+43 | | -7=3+2/3x | | -5=x-1/5 | | -5(4x-4)=4(5-5x)+0 | | -4.68=u/6+3 | | 6(1+3m)=-8(5-2m)-4 | | X2+3x+1=4x+3 | | 3a+7a=-5+4a-1 | | 5(x-57)+15=15 | | 2/3(c-1)=2c+1/2 | | 1.1+w/7=-16.4 | | 9.8=6.1+-d | | 8(2y+6)5y=37 | | -2(-4x–8)=-29–7x | | (x+7)+7=180 | | x+2x-12=12-5x | | 3(i-3)-(4i)=-13 | | -2(5x+4)=5(4-2x)-28 | | 4x+5+3x+13=180 | | -4x-15=46 | | 3r–3+2r=13–3r |

Equations solver categories